Gross Anatomy, Histomorphology and Histochemistry of Equine Umbilical Cord - Kumar, Pawan; Gulati, Baldev R.; Deep, Aman; Kumar, Rajesh; Mohanty, Niharika; Anand, Taruna; Yadav, P. S. (Indian Journal of Veterinary Anatomy, 2013)
The umbilical cords collected at the time of foaling of Thoroughbred mares presented tortuous course due to curving of umbilical arteries and veins and measured 55-65 cm from ligation site of foal to the attachment of placenta. Formalin-fixed tissues of umbilical cord having artery, vein and urachus were processed to make 5-6 µ paraffin sections. The umbilical cord was mainly comprised of two central umbilical arteries and two peripheral umbilical veins along with allantoic duct (urachus) and Wharton’s jelly towards juxtaplacental region. However, a single umbilical vein formed by fusion of two veins was observed towards juxtafoetal portion. The thickness of walls of umbilical artery was greater than that of umbilical vein. Histo-architecture of umbilical artery, vein and Wharton’s jelly varied at different sites of extent and presented varying qualitative affinities for mucopolysaccharides.